Теоретико-методологічні засади дослідження франчайзингу - Голубка Д. С. (НТУ "ДП", 2023)
Результати. Проаналізовано дослідницькі кластери в історіографії франчайзингу, що дозволило сформувати теоретичну платформу його вивчення. Остання включає систему теорій щодо передумов розвитку (глобалізації, конкуренції, «push-pull» факторів, підприємництва, мережевих структур) та особливостей франчайзингу. Теорії, які обґрунтовують особливості франчайзингу, запропоновано поділяти на дві групи за критерієм відображення ними: залучення й використання ресурсів (теорії щодо відносин (агентства, сигналів, інституційна, зацікавлених сторін), а також прийняття рішень (трансакційних витрат, еклектичної парадигми, підприємницької орієнтації). Визначено, що найбільш поширеною є теорія агентства, яка пояснює закономірності відносин й послаблення розбіжностей сторін, коли один суб’єкт-виконавець представляє відносини іншого-замовника через делегування повноважень у прийнятті рішень, виконанні операцій, фінансовому плануванні, менеджменті інвестиційного портфеля та ін. Зважаючи на основу відносин у виникненні франчайзингу та їхнього значення для успішності бізнесу, актуалізовано важливість положень концепції довіри. Продемонстровано, що вона продовжує розвиватись в системі теоретичних положень про партнерство у франчайзингу, враховуючи нові виклики глобальної нестабільності, що посилились після пандемії Covid-19, повномасштабного російського вторгнення в Україну та загострення інших міжнародних конфліктів. Results. Research clusters in the historiography of franchising were analyzed, which made it possible to form a theoretical platform for its study, which includes a system of theories regarding development prerequisites (globalization, competition, «push-pull» factors, entrepreneurship, network structures) and features of franchising. It is proposed to divide the theories that substantiate the specifics of franchising into two groups according to the criterion of their reflection: attraction and use of resources (theories regarding relations (agency, signals, institutional, stakeholders), as well as decision-making (transaction costs, eclectic paradigm, entrepreneurial orientation). It was determined that the most widespread is the theory of agency, which explains the regularities of relations and the weakening of the parties’ disagreements, when one executing entity represents the relations of another customer through the delegation of powers in decision-making, execution of operations, financial planning, investment portfolio management, etc. Considering the basis of relationships in the emergence of franchising and their importance for business success, the importance of the provisions of the concept of trust is updated. It is demonstrated that it continues to develop in the system of theoretical provisions on partnership in franchising, taking into account the new challenges of global instability, which have increased after the Covid-19 pandemic, the full-scale Russian invasion of Ukraine and the exacerbation of other international conflicts.
Theoretical and methodological fundamentals of studying franchising
Keywords: міжнародні економічні відносити; франчайзинг; дослідницькі кластери; історіографія франчайзингу; концепція довіри; модель організації бізнесу; international economic relationships; franchising; research clusters; historiography of franchising; the concept of trust; business organization model